An equation for hole-spanning design of underground cast iron pipes lined with polymeric liners. (May 2022) - Fu, Guoyang; Shannon, Benjamin; Deo, Ravin; Azoor, Rukshan; Kodikara, Jayantha
Highlights: Effect of holes in cast iron pipes on lined pipe performance is numerically studied. An equation for the maximum stresses in polymeric liners for lined pipes is derived. Maximum liner stress increases with hole size before a threshold value is reached. Increasing liner thickness and friction coefficients reduces maximum liner stress. Increasing liner modulus increases maximum liner stress considerably. Abstract: Defects such as through-wall holes may significantly affect the performance of cast iron pipes lined with polymeric liners. Literature review reveals that the hole spanning design formulae in the Appendix X1 of ASTM F1216 (2016), also adopted in AWWA (2019), produce conservative results for holes with diameters smaller than the cut-off value defined in ASTM F1216 (2016) and AWWA (2019) for partially and fully deteriorated pipes but unconservative results for holes with diameters larger than the cut-off value, and the effect of holes on the mechanical behaviors of lined water pipes has not been thoroughly investigated. This paper aimed to address the issue in the hole spanning design formulae in ASTM F1216 (2016) and AWWA (2019), and numerically investigated and quantified the effect of holes in cast iron host pipes on the performance of lined pipes. A wide range of pipe dimensions, hole diameters, liner modulus, liner wall thickness, internal pressure and friction coefficients at the interface between the cast iron pipe and liner were considered. An equation for the maximum stresses in polymeric liners was derived based on the numerical results. It was found that the maximum stress in the polymeric liner increases with the diameter of the hole in the cast iron pipe until the hole size reaches a threshold level where the effect of hoop stresses takes over and the maximum stress will tend to plateau. It was also found that increasing the friction coefficient, the ratio of pipe modulus to liner modulus and the liner wall thickness will reduce the maximum stress in the liner. The outcome of this study can assist engineers in more accurate hole spanning design of polymeric liners for deteriorated cast iron pipes and quantifying the size of an unacceptable hole for a given host pipe and a liner product.